The Players' Realm : studies on the culture of video games and gaming - Smith, Jonas Heide; Williams, J. Patrick (Jefferson McFarland & Company, 2007)
This study sketches some of the various trajectories of digital games in modern Western societies, looking at the growth and persistence of the moral panic that continues to accompany massive public interest in digital games. The book continues with a new phase of games research exemplified by systematic examination of specific aspects of digital games and gaming.
Keywords: Videojuegos -- Aspectos sociales